# Solve this system of equations using the addition/elimination method. 5x-2y=-10 3x-6y=66

### 1 Answer | Add Yours

Multiply each equation by the value that makes the coefficient of y equal. Do this by dividing the least common multiple of the coefficient of y by the current coefficient. The least common multiple is 6.

Then add the two equations together to eliminate y from the system.

Finally, substitute the value found for x into the original equation to solve for y.

`-3(5x-2y=-10)rArr-15x+6y=30`

`3x-6y=66rArr3x-6y=66`

` -12x=96`

`x=-8`

`3(-8)-6(y)=66`

`-24-6y=66`

`-6y=90`

`y=-15`

**`x=-8, y=-15`**

``

``